68Ga-DOTATATE Uptake in COVID-19 Pneumonia: A Non-Neoplastic False Positive - Joshua P. Weissman; Twyla Bartel (World Journal of Nuclear Medicine)
In the detection and characterization of neuroendocrine tumors (NETs), the NETSPOT 68Ga-DOTATATE positron emission tomography/computed tomography (PET/CT) utilizes a somatostatin analog to capture whole body imaging of somatostatin receptors. Here, we report a rare case of incidental coronavirus disease 2019 (COVID-19) detection using 68Ga-DOTATATE PET/CT for a 48-year-old patient with COVID-19 who presented to our nuclear medicine department for oncologic and neuroendocrine indications. Current maximal intensity project image from 68Ga-DOTATATE PET/CT demonstrated numerous hypermetabolic foci in the upper abdominal lymph nodes, consistent with somatostatin-avid pancreatic islet cell neoplasm. Radiotracer uptake corresponding to the anatomic infiltrates was also seen in the bilateral pneumonia. With the rise of worldwide COVID-19 cases, and the continued use of NETSPOT for somatostatin avid neoplasms, it is imperative that diagnostic measures of this disease are clearly understood. This case highlights the importance of including COVID-19 on the differential diagnosis when radiotracer uptake appears in 68Ga-DOTATATE PET/CT.